Characterization of archaeometallurgical artefacts by means of portable Raman systems: corrosion mechanisms influenced by marine aerosol. (8th August 2016) - Veneranda, M.; Aramendia, J.; Gomez, O.; Fdez‐Ortiz de Vallejuelo, S.; Garcia, L.; Garcia‐Camino, I.; Castro, K.; Azkarate, A.; Madariaga, J. M.
Abstract : This work focuses on the analytical study of eight medieval metallic artefacts discovered during the archaeological excavations of the Ereñozar necropolis (13th century, Basque Country, Spain). As the conservation state of archaeological objects is closely related to the characteristics of the burial environment, chromatographic analysis was performed with the aim of quantifying the soluble salt content of the burial ground. Moreover, portable systems were used for the elemental and molecular characterization of the artefact collection. A hand‐held X‐ray fluorescence spectrometer was used to analyse the alloys constituting the objects. Then, the characterization of the main corrosion phases affecting the artefacts was carried out using two portable Raman systems. Both tools, equipped with different excitation lasers (785 and 532 nm respectively), were used in a complementary way by coupling them with the BAC151B video microscope. Thanks to its dual laser wavelength port, it was possible to sequentially focus with both lasers on the same selected spot. In this way, the sensitivity of each system for the characterization of Fe‐based and Cu‐based corrosion phases was also compared. Furthermore, the information obtained from both chromatographic and spectroscopic techniques allows the modelling of the chemical reactions that led to the formation of the identified degradation products. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The main corrosion phases affecting several archaeometallurgical artefacts proceeding from the Ereñozar necropolis (13th century, Basque Country, Spain) were characterized through the use of portable Raman systems. Thanks to the dual laser wavelength port of the coupled BAC151B video microscope, it was possible to focus on the same spots of analysis with both 532 and 785 nm lasers. The obtained results emphasize that by using different excitation sources in a complementary way, it is possible to maximize the molecular information provided by Raman spectroscopy.